Empirically based guidelines for goal-finding procedures in psychotherapy: Are some goals easier to attain than others? - Berking, Matthias; Grosse Holtforth, Martin; Jacobi, Claus; Kroener-Herwig, Birgit (Psychotherapy Research, 2005)
Treatment goals are either proposed by a patient or deduced from the case formulation of the therapist. To optimize goal-finding procedures in psychotherapy, therapists need an empirical point of reference to estimate the degree of goal attainment that can be expected for a specific treatment goal. To establish such an empirical basis, treatment goal categories of the primary treatment goals of 2,770 inpatients undergoing cognitive-behavioral therapy were categorized by the Bern Inventory of Treatment Goals. The levels of goal attainment were then compared with respect to 48 different goal categories. The results indicate that goal attainment differs according to treatment goal categories, even if confounding characteristics of the patient are controlled for. © 2005 Society for Psychotherapy Research.
Created from Fastlane, Scopus look-up